DNA as a quantum system in evolution - Nahuel Aquiles Garcia (PLoS ONE, 2026)
Time may be viewed as an emergent consequence of increasing information entropy. I explore a toy quantum‑information model in which DNA is treated as an open quantum system. In this framework, weak, time‑dependent perturbations (potentially arising from thermal fluctuations, ionic microfields, metabolic noise, or electromagnetic signals) bias the micro‑timing of events during replication and repair. These slight timing shifts can influence the fate of transient electronic and protonic configurations (including short‑lived tautomeric states driven by proton‑transfer tunnelling), subtly altering mutation probabilities. To test this idea, I map nucleotides in the Mycobacterium tuberculosis genome to constrained qubit states and quantify informational structure using Shannon and von Neumann entropies and coding to non‑coding correlation metrics. Simulations of Hamiltonian dynamics under physiologically plausible perturbations show that real genomic segments exhibit distinctive dynamical signatures compared with controls. I also examine a variant in which a weak, slowly varying external signal is introduced as a background “beat” against which DNA dynamics can be compared. Because a Doppler shift in electromagnetic waves encodes the flow of time through the relative motion of source and observer, a cosmic microwave background (CMB) with a tiny frequency drift provides a conceptual clock and a source of informational entropy: it feeds a time‑correlated input into the DNA quantum system, allowing the molecule to sample cosmic time and translate it into a biological scale by modulating tunnelling probabilities and thus mutation patterns. This CMB‑inspired drive is simply a convenient illustration; the model does not rely on it, and other sources of weakly structured entropy could be tested. Across simulations, sequence‑dependent responses to both intrinsic and structured perturbations generate testable predictions: changing the structure or timing of these weak perturbations should produce reproducible shifts in mutation spectra. This framework connects cellular ageing and evolution to the flow of cosmic time and suggests experiments to probe DNA’s sensitivity to time‑dependent perturbations.